The application of artificial intelligence languages in business intelligence for the prediction of COVID-19 data. - Sara EL HABBARI, M'hamed-amine SOUMIAA, Mohamed MANSOURI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since the discovery of artificial intelligence, information systems are constantly evolving, especially decision-making ones. Thanks to AI, today’s decisionmaking tools treat in a more effective manner massive data, real-time analysis, and optimize the decision-making process of companies in the short and medium-term. To further optimize the profits of these companies, it is necessary to enrich their decision-making platforms with predictive visions using some advanced AI technologies. This is what we are going to discuss in detail throughout this article